MALOCCLUSION TREATMENT CLASS II DIVISION 1 WITH MINISCREWS - Camacho Guevara, Juan (2016)
This case report describes the diagnosis and treatment of a male patient 15 years old, who was treated at the National Institute of Child Health, with a malocclusion Class II Division 1 characterized by a deep bite, a class II skeletal relationship by mandibular retrusion, and maxillary protrusion, convex profile and lip protrusion. The objective was to improve the facial profile, the aesthetics of the smile and to achieve stable occlusal relationships. Treatment involved the extraction of first premolars and miniscrews anchorage for space closure and deep bite correction (retraction and intrusion of upper incisors). The duration of treatment was 30 months. Orthodontic compensatory treatment was emphasized as an alternative to the ideal ortho –surgical treatment .Acceptable results were achieved in the reduction of overjet and the improvement of facial profile.